Effect of Emotional Intelligence Program to Improve Academic Performance Among Nursing Students of Selected Colleges - Punam Vinayak Walunj; Barse Nikita Prakash; Tejas Sanjay Anap; Abhishek Rajendra Balte; Vrushali Ashok Bhosale; Prathmesh Shivaji Bhuse; Sandesh Suresh Shirsath (International Journal of Evidence Based Nursing And Practices, 2024)
Introduction: Emotional intelligence involves understanding one’s own feelings as well as those of others and reacting appropriately in different situations. It represents a form of social intelligence characterized by the ability to observe and distinguish between emotions, both personal and others', and to leverage this insight to inform decision-making and behavior. Materials and Method: An experimental study design is used in the research. The study was conducted at selected nursing colleges. The population included nursing students. The total population size is 40. The study recruited participants using a non-probability simple random sampling method. Results: The finding of the study shows that mean of effectiveness of emotional intelligence scale in pre-test is 75.12 and in post-test is 83.4, median of effectiveness emotional intelligence scale in pre-test is 77.5 and in post-test is 86, standard deviation in pre-test is 10.2886 and in post-test is 6.7169. The mean of the academic performance in pre-test is 9 and in post-test is 9.625, median in pretest is 15 and in post-test is 17.5, standard deviation in pretest is 1.9986 and in post-test is 1.9039. The mean of academic performance scale in pre-test is 15.4 and in post-test is 17.5, median in pre-test is 15 and in post-test is 16, standard deviation in pre-test is 5.9130 and in post-test is 6.7069. Conclusion: Findings of the study showed that there is a positive significant effect of emotional intelligence program to improving academic performance. The study revealed that higher emotional intelligence is significantly related to better academic achievement among students.
Keywords: Emotional intelligence; academic performance; effectiveness; emotional intelligence program